Defending the U.S. air transportation system against chemical and biological threats (National Academies Press, 2006)
"The Committee on Assessment of Security Technologies for Transportation was appointed by the National Research Council (NRC) in response to a request from the Transportation Security Administration (TSA) for a study of technologies to protect the nation's air transportation system from terrorist attacks. The committee judged that the best way to provide a timely response would be to produce a series of short reports on promising technologies, focusing on specific topics of greatest interest to the sponsor. This is the second of four such topical reports, all of which focus on air transportation security. The committee believes that the air transportation environment provides a test case for the deployment of security technologies that could subsequently be used to protect other transportation modes as well. The discovery in February 2004 of the biological poison ricin in a Senate office building in Washington, D.C., highlights the fact that the terrorist's arsenal now includes not only the all-too-familiar weapons such as small arms and explosives, but also chemical and biological agents. This expanding arsenal demands that policy makers and transportation authorities consider the deployment of new defensive technologies to respond to the new threats. In this report, the committee explores defensive strategies that could be used to protect air transportation spaces (specifically, airport terminals and aircraft) against attack with chemical or biological agents and makes recommendations with respect to the role of TSA in implementing these strategies."--Excerpted from preface